IMPROVEMENT OF STUDENTS' CRITICAL THINKING SKILLS AS AN IMPACT OF THE APPLICATION OF THINK TALK WRITE ON EARTH AND SOLAR SYSTEM - Nufus, Fitrotin; Hartiningsih, Try; Ahied, Mochammad; Wahyuni, Eva Ari; Putera, Dwi Bagus Rendy Astid (Jurnal Pembelajaran Sains, 2024)
This research aimed to determine whether the Think Talk Write model increased students' critical thinking skills regarding the earth and solar system. A quasi-experimental research design was used, specifically Nonequivalent Control Group Design. The study was conducted at Al-Kholiliyah Bangkalan Middle School during the 2023/2024 academic year, involving all class VII students. The VII-A cohort served as the experimental class, where the Think Talk Write model was implemented, while the VII-B cohort served as the control class, where direct instructional method was used. Purposive sampling was employed to select the sample groups. The N-Gain Score test was utilised to analyze the improvement in critical thinking skills. The results show a significant increase in critical thinking skills among students in the experimental class, with 100% achieving an improvement categorized as medium. In contrast, the control class showed only 7.14% improvement in medium category, with 85.71% of students falling into the low improvement category.